THE EFFECT OF LEADERSHIP STYLE AND MOTIVATION ON THE PERFORMANCE OF POLICE MEMBERS WITH DISCIPLINE AS INTERVENING VARIABLES IN POLDA KEPRI - Kenedy, T. Fazrial; Indrayani, Indrayani; Khaddafi, Muammar; Astriani, Fitri (RADJA PUBLIKA, 2022)
Human Resources (HR) is one of the most important instruments in an organization. In the face of today's fierce competition, globalization. The success or failure of an organization in achieving its goals is very dependent on the ability of Human Resources (HR) in carrying out the tasks assigned by the organization. Because HR is one of the most important instruments in an organization that can motivate members to improve performance. To be able to improve the productivity of human resources better, agency management must and is required to be able to manage human resources optimally. In this study using quantitative research. Analysis of the data used in this study using an explanatory research approach. This research uses SmartPLS software.